2007
DOI: 10.1098/rsif.2007.1114
|View full text |Cite
|
Sign up to set email alerts
|

Landscape epidemiology of plant diseases

Abstract: Many agricultural landscapes are characterized by a high degree of heterogeneity and fragmentation. Landscape ecology focuses on the influence of habitat heterogeneity in space and time on ecological processes. Landscape epidemiology aims at applying concepts and approaches originating from landscape ecology to the study of pathogen dynamics at the landscape scale. However, despite the strong influence that the landscape properties may have on the spread of plant diseases, landscape epidemiology has still rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
195
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(206 citation statements)
references
References 95 publications
(107 reference statements)
3
195
0
3
Order By: Relevance
“…Pathogens are vector-, soil-or air-borne, thus landscape elements act as corridors or conversely as barriers (Plantegenest et al, 2007). At the local scale, Mundt et al (2007) reported that, whatever the field size, mixing host and non-host plants (i.e.…”
Section: Pathogensmentioning
confidence: 99%
“…Pathogens are vector-, soil-or air-borne, thus landscape elements act as corridors or conversely as barriers (Plantegenest et al, 2007). At the local scale, Mundt et al (2007) reported that, whatever the field size, mixing host and non-host plants (i.e.…”
Section: Pathogensmentioning
confidence: 99%
“…Disease incidence depends on the abundance of inoculum reservoirs in the surrounding fields, which influences pathogen spread and pressure [17,40]. A high proportion of semi-natural habitats in the landscape probably limited the abundance of inoculum reservoirs (e.g.…”
Section: (A) Effects Of Soil Management On Ecosystem Service Provisionmentioning
confidence: 99%
“…[16]). Moreover, landscape composition can greatly affect spatial dynamics of crop pathogens and weeds, influencing inoculum and propagule pressure and hence the risks of crop infection and weed invasion [17,18]. Interactions between local management and landscape composition have been principally investigated in relation to one specific service (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of pesticides has not completely prevented pest outbreaks and subsequent losses of yield (Wilson et al 2001;oerke 2006), because the pests have either become resistant to pesticides and/ or there has been a breakdown in ecological processes like pollination, ecological functioning of the soil and biological control (lewis et al 1997;Plantegenest et al 2007). in addition, there are many reports of pesticides adversely affecting man (benton 2003;lee 2004;ameixa and Kindlmann 2011a).…”
Section: Introductionmentioning
confidence: 99%